INTERPRETATIONS AND TRANSLATIONS OF RUMI'S POETRY (International Journal of Food and Nutritional Sciences, 2022)
This study explores the Interpretations and Translations of Rumi's Poetry. Rumi’s poetry offers a rich tapestry of insights into his profound mystical and spiritual work. Rumi, a 13th-century Persian poet and Sufi mystic, is renowned for his exploration of divine love, spiritual enlightenment, and the human condition. His poetry, written in Persian and laden with cultural and religious references, presents unique challenges and opportunities for interpretation and translation. Interpretations of Rumi’s poetry often emphasize its mystical and philosophical dimensions, reflecting on themes such as the soul’s longing for union with the Divine, the symbolism of divine love, and the transcendence of the ego. These interpretations reveal the depth of Rumi’s spiritual insights and the universality of his messages, which resonate with diverse audiences across various cultural and religious contexts.Translations of Rumi’s poetry add another layer of complexity. Literal translations strive to maintain the integrity of the original Persian text, preserving its linguistic and cultural nuances, but may struggle with accessibility and poetic flow. Interpretive translations, on the other hand, prioritize conveying the emotional and spiritual essence of the poems, often adapting them to contemporary sensibilities and broader audiences. Notable translators such as Coleman Barks, A.J. Arberry, and Reynold A. Nicholson have each contributed uniquely to the global appreciation of Rumi’s work, reflecting their own perspectives and approaches. The impact of these translations and interpretations is significant, influencing how Rumi’s poetry is understood and appreciated worldwide. They facilitate engagement with his work across different cultural and spiritual landscapes, ensuring that his timeless messages of love, unity, and spiritual awakening continue to inspire and resonate with readers around the globe.